2014
DOI: 10.1287/mnsc.2013.1816
|View full text |Cite
|
Sign up to set email alerts
|

Managing Global Sourcing: Inventory Performance

Abstract: T he use of global suppliers has increased considerably over the last three decades. Operations management theory establishes that global sourcing requires more units of inventory, but since these units are often procured at a lower cost from global suppliers the capital invested in inventory and the consequent financial burden may increase or decrease with global sourcing. This study provides rigorous firm-level empirical evidence that links the global sourcing practices of public U.S. firms and their invento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(102 citation statements)
references
References 40 publications
1
101
0
Order By: Relevance
“…In other words, overseas (vs. domestic) production increases inventory levels. Similarly, Jain et al. (2013) using firm level data found that outsourcing from global sources results in an increase in inventory investment.…”
Section: Theory and Hypothesesmentioning
confidence: 96%
“…In other words, overseas (vs. domestic) production increases inventory levels. Similarly, Jain et al. (2013) using firm level data found that outsourcing from global sources results in an increase in inventory investment.…”
Section: Theory and Hypothesesmentioning
confidence: 96%
“…Other papers on inventory management employ single equation models, including those by Ton and Raman (2010), Randall et al (2006), Rumyantsev and Netessine (2007), and Jain et al (2013). Industry-specific papers include those by Olivares and Cachon (2009) and Cachon and Olivares (2010), which identify the key drivers that explain the variation in the finished goods inventory within the automotive distribution system.…”
Section: Supply Chain Management (Onlinementioning
confidence: 99%
“…Using variational inequality theory, the authors formulate the governing equilibrium conditions of the competing manufacturers, and a simulation study investigates the quantitative impact of demand and cost uncertainty. Recent empirical work by Jain et al (2014) studies the impact of global sourcing and supplier diversification on inventory investment.…”
Section: Related Literaturementioning
confidence: 99%